Pengaruh Komitmen Organisasi Dan Pengembangan Karir Terhadap Kinerja Pegawai Pada Kantor Badan Penanggulangan Bencana Daerah (BPBD) Kabupaten Sikka - Regina Aurelia Wanda; Antonius Philippus Kurniawan; Viktor Eko Transilvanus (Jurnal CUAN Universitas Nusa Nipa Maumere, 2025)
This study aimed to : (1) describe employee performance, organizational commitment, and career development; (2) analyse the influence of organizational commitment and career development on employees performance both partially and simultancousy. The population of this study consisted of 35 employees at the Regional Disaster Management Agency (BPBD) Office of Sikka Regency. Due to the limited population,a census of saturated sampling method was employed. Data were colleted through quenstionnaires and analysed usimg descriptive medthos and inferential statistics, specifically multiple linear regression. Hypothesis testimg was conducted using F-tests and t-tests. The descriptive analysed results indicated that the variables of employee performance, organizational commitment, and career development were categorized as good.The t-tests statistics showed that, partially, the organizational commitment variable had a significant positive effect on employee performance. The F-tests results indicated that, simultaneously, the variables of organizational commitment and career development had a significant positive effect on employee performance. The determination analyzed results showed that the two independent variables in this study were able to explain 28,4%b of the variation in employee performance at the Regional Disaster Management Agency (BPBD) Office of Sikka Regency.